2010
DOI: 10.1093/cvr/cvq373
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite induces HMGB1 release by cardiac cells in vitro and HMGB1 upregulation in the infarcted myocardium in vivo

Abstract: These findings indicate that peroxynitrite represents a key mediator of HMGB1 overexpression and release by cardiac cells and provide a novel mechanism linking myocardial oxidative/nitrosative stress with post-infarction myocardial inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 50 publications
5
61
0
Order By: Relevance
“…Loukili, et al showed that the expression of HMGB1 in hearts increased significantly after 1 hour of reperfusion, further increased after 2 hours of reperfusion, and then no further increase was observed thereafter. 13) As we showed in this study, P.g. infection significantly elevated serum HMGB1 levels on day 5, but not on day 14.…”
Section: Discussionsupporting
confidence: 64%
“…Loukili, et al showed that the expression of HMGB1 in hearts increased significantly after 1 hour of reperfusion, further increased after 2 hours of reperfusion, and then no further increase was observed thereafter. 13) As we showed in this study, P.g. infection significantly elevated serum HMGB1 levels on day 5, but not on day 14.…”
Section: Discussionsupporting
confidence: 64%
“…HMGB1 also forms various complexes with many different molecules in the extracellular milieu, promoting additional pro-inflammatory activities through interaction with TLR2, TLR3, TLR9, and the IL-1 receptor (Bianchi, 2009;Janko et al, 2013). HMGB1 plays significant roles in the pathophysiology of sterile inflammation (Andersson and Tracey, 2011) associated with diverse acute and chronic conditions, including myocardial infarction (Loukili et al, 2011), hepatic ischemia (Tsung et al, 2005), stroke (Schulze et al, 2013), circulatory shock and trauma (Andersson and Tracey, 2011), diabetes (Nogueira-Machado et al, 2011), cancer (Krysko et al, 2012), and arthritis (Harris et al, 2012), and it also acts as a key pro-inflammatory cytokine involved in the pathogenesis of sepsis (Yang et al, 2004). Thus, HMGB1 emerges as a central acting mediator at the intersection between sterile and infectious inflammation (Andersson and Tracey, 2011).…”
Section: Role Of Oxidative Stress In Inflammationmentioning
confidence: 99%
“…In a study using isolated cardiomyocytes in vitro, we reported that exposure of the cells to toxic concentrations of peroxynitrite induced necrotic cell death and was associated with the release of copious amounts of HMGB1 (Loukili et al, 2011). Similarly, Tang et al (2007Tang et al ( , 2011 reported that treatment of various mouse and human cell lines with H 2 O 2 promoted significant extracellular HMGB1 release, whereas Tsung et al (2007) showed that oxidants promoted the active release of HMGB1 by cultured hepatocytes through calmodulin-dependent kinase signaling.…”
Section: Role Of Oxidative Stress In Inflammationmentioning
confidence: 99%
“…Tsung et al (14) further demonstrated that the release of HMGB1 from cultured hepatocytes was also found to be an active process regulated by ROS. Recently, Loukili et al (15) showed that peroxynitrite, a potent cytotoxic oxidant, was involved in the release of HMGB1 in cardiac cells. Hence, inhibiting ROS may cause suppression of HMGB1 expression.…”
Section: Discussionmentioning
confidence: 99%